Comparison of ferrate and ozone pre-oxidation on disinfection byproduct formation from chlorination and chloramination. (1st June 2019) - Jiang, Yanjun; Goodwill, Joseph E.; Tobiason, John E.; Reckhow, David A.
Abstract: This study investigated the effects of ferrate and ozone pre-oxidation on disinfection byproduct (DBP) formation from subsequent chlorination or chloramination. Two natural waters were treated at bench-scale under various scenarios (chlorine, chloramine, each with ferrate pre-oxidation, and each with pre-ozonation). The formation of brominated and iodinated DBPs in fortified natural waters was assessed. Results indicated ferrate and ozone pre-oxidation were comparable at molar equivalent doses for most DBPs. A net decrease in trihalomethanes (including iodinated forms), haloacetic acids (HAAs), dihaloacetonitrile, total organic chlorine, and total organic iodine was found with both pre-oxidants as compared to chlorination only. An increase in chloropicrin and minor changes in total organic bromine yield were caused by both pre-oxidants compared to chlorination only. However, ozone led to higher haloketone and chloropicrin formation potentials than ferrate. The relative performance of ferrate versus ozone for DBP precursor removal was affected by water quality (e.g., nature of organic matter and bromide concentration) and oxidant dose, and varied by DBP species. Ferrate and ozone pre-oxidation also decreased DBP formation from chloramination under most conditions. However, some increases in THM and dihaloacetonitrile formation potentials were observed at elevated bromide levels. Graphical abstract: Image 1 Highlights: Fe(VI) and O3 pre-oxidation are comparable at similar molar doses for most DBPs. Ozone led to higher haloketone and chloropicrin formation than Fe(VI). Fe(VI) performed better than O3 in water with high SUVA and low bromide. Fe(VI) and O3 increased DHAN formation in bromide rich water with chloramination.